Analisis Ekspor Kelapa dan Produk Olahan Kelapa Indonesia di Pasar Uni Eropa: Pendekatan Indeks Spesialisasi Perdagangan - Riska Dian Oktari; Abi Pratiwa Siregar; Deny Meitasari (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2023)
Coconut is a plantation commodity that Indonesia exports to European Union countries. Most of Indonesia's coconut exports are in the form of processed coconut products. This study aims to determine the competitive position of coconut and its processed products from Indonesia in the European Market. This research was conducted from July 29 to August 18, 2020. The object of this research is the export of Indonesian crude coconut oil (HS code 151311), fractions of coconut oil and semi-finished coconut oil (HS code 151319), coconut (HS code 080111) and young coconut HS 080119). The analysis used in this research is Trade Specialization Index (TSI) method to measure Indonesia's competitive position in European Union countries as an export destination for coconut commodities and their processed products. The results showed that coconut commodities and processed coconut products generally show strong competitiveness and are at the maturity stage.